Free ports: towards a network of trade gateways - Alexandre Lavissière; Jean-Paul Rodrigue (Journal of Shipping and Trade (JST), 2017)
Free ports are a form of territorial exceptionalism that has existed for centuries and become an important paradigm of globalization. In the contemporary setting, they act as transportation, logistics and trade platforms, using their territorial exceptionalism as a competitive advantage. Free ports such as Hong Kong, Singapore and Dubai are among the world's leading commercial gateways, offering a form of leverage to transactions, transportation and the transformation of material goods. The historical evolution of free ports underlines a growing complexification and specialization that has led to a multitude of models, each fitting a specific regulatory and operational framework.This paper aims rationalizing the complexity of free ports. It is based on a wide array of empirical observations and an analysis of structure, function and evolution of free ports. Collected free ports data enabled the identification of three constitutive factors of evolution: an external factor (the jurisdiction), an internal factor (the services provided) and a linking factor (the orientation of flows). Based on these three factors a model of free ports was designed with a typology of thirteen types of free ports, an explanation of their evolution, and their future prospects.
Keywords: 650; Free port; Foreign trade zone; Gateway; Port; Globalization; Logistics network